2019
DOI: 10.3390/coatings9120868
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Retrieved Cementless Femoral Hip Endoprostheses Produced from a Ti6Al7Nb Alloy

Abstract: We have investigated new and retrieved cementless hip endoprostheses that prematurely failed due to (i) aseptic loosening, (ii) infection and (iii) latent infection. The aim was to better understand the physico-chemical phenomena on the surfaces and sub-surfaces of the Ti6Al7Nb alloy implant. The results of our studies should enable us to distinguish the causes of premature failure, optimize the surface modification, achieve optimal osseointegration and extend the useful lifetime of the implants. The surface p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Another issue that challenges its successful application in some fields is the potential presence of locked shot particles on the shot-peened surfaces introducing potential crack nucleation sites (Figure 23). In biomedical applications, these particles could be responsible for early implant failure [158]. application in some fields is the potential presence of locked shot particles on the shotpeened surfaces introducing potential crack nucleation sites (Figure 23).…”
Section: Combination Of Shot Peening and Electropolishingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another issue that challenges its successful application in some fields is the potential presence of locked shot particles on the shot-peened surfaces introducing potential crack nucleation sites (Figure 23). In biomedical applications, these particles could be responsible for early implant failure [158]. application in some fields is the potential presence of locked shot particles on the shotpeened surfaces introducing potential crack nucleation sites (Figure 23).…”
Section: Combination Of Shot Peening and Electropolishingmentioning
confidence: 99%
“…application in some fields is the potential presence of locked shot particles on the shotpeened surfaces introducing potential crack nucleation sites (Figure 23). In biomedical applications, these particles could be responsible for early implant failure [158]. The topography of a surface-treated Ti-6Al-4V alloy is modified by shot grains penetrated into the surface layer.…”
Section: Combination Of Shot Peening and Electropolishingmentioning
confidence: 99%
“…Previous studies indicate that the surface properties of the implant including particle debris that forms in processing of the implants may have important impact on the adjacent cells when implanted in the body (Jenko et al, 2017, Feizpour et al, 2019. It is of particular interest to analyse the effect of small particles that are formed in the processing of the implants and particles found on the surface of retrieved implants that underwent fail-ure (Avsec et al, 2019). We focused on the effect of micron-sized particles of Al2O3, TiO2 and hydroxyapatite (HA) on inflammatory, oxidative stress-related features in two cultures of human umbilical vein endothelial cells -HUVEC cells.…”
Section: Implant Debris Associated Inflammation Oxidative Stress and ...mentioning
confidence: 99%
“…The study of new and retrieved dental implants and restorative materials-commercially pure titanium (cpTi), the Ti 6 Al 4 V alloy and CoCrMo-by light microscopy, SEM and energy-dispersive spectroscopy, showed that the surfaces of the Ti and Ti 6 Al 4 V implants were affected by corundum blasting [20,21]. Moreover, contamination of the new and early removed femoral components made of the alloy Ti 6 Al 7 Nb with corundum wear particles was found also 5 to 20 µm below the surface [22], as the hard corundum wear particles were embedded into a softer matrix of Ti 6 Al 7 Nb alloy during the sandblasting process. The microstructural analysis of the cross-sections showed that the cracks around the built-in particulate matter range to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Such cracks allow corrosion and represent sites for the attachment and colonization of bacteria, the formation of biofilm, periprosthetic infection and implant failure. Therefore, in addition to aseptic loosening of the implant, the corundum particles can cause periprosthetic infection [22]. As unavoidable generation of wear debris from any part of a prosthesis leads to prosthesis failure, histological analysis of the tissue obtained during implant revision surgery is considered important for wear-particle identification, and for the classification of biological reactions to wear particles [23].…”
Section: Introductionmentioning
confidence: 99%